Kekuatan Pembuktian Keterangan Ahli Berdasarkan Hukum Acara Perdata Indonesia - Jayadi, Hendri (Fakultas Syariah INSURI Ponorogo, 2023)
The purpose of this research is to evaluate the validity of expert testimony based on Indonesian civil procedural law in Indonesian civil law. The method used is descriptive and qualitative. The data collection technique is a documentary study. The data used is secondary data in the form of documentation of the regulations used. The results of the study show that the position of an expert can be part of the witnesses who provide information in the context of evidence. Provisions regarding an expert witness are explained in Article 154 HIR. This makes the role of an expert important in explaining the problem under discussion. In terms of strength in the context of civil law, an expert has been screened through two commitments, namely a moral commitment (through an oath or promise) and also a professional commitment (which includes the expert's technical expertise through education or experience). In addition, the strength of an expert's statement is also higher because it is tested by the Public Prosecutor (Prosecutor) and also legal counsel.